Pengaplikasian Gelombang Elektromagnetik dan Nanopartikel Dielectric dalam Peningkatan Pemulihan Minyak - Riyan Aditya; Dafairro Abbil Gunawan; Della Saskia Amelia; Syarif Hidayatullah; Diyajeng Luluk Karlina (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Enhanced oil recovery (EOR) is the recovery of oil remaining in a reservoir after primary and secondary recovery methods because it has been exhausted or is no longer economical, using thermal, chemical or mixed gas processes. Most conventional methods are not suitable for extracting oil from high temperature and high pressure (HTHP) reservoirs due to chemical degradation in the environment. Alternatively, electromagnetic (EM) energy is used as a thermal method to reduce oil viscosity in reservoirs, thereby increasing oil production. The application of nanotechnology in EOR is also investigated. In this study, we investigate a non-invasive method by injecting dielectric nanofluids into an oil reservoir simultaneously with electromagnetic irradiation, with the aim of increasing oil production by causing disruption at the oil-water interface. During core displacement tests, ZnO and Al2O3 nanofluids were shown to obtain higher amounts of residual oil than commercial sodium dodecyl sulfate (SDS) surfactant without EM irradiation. With EM irradiation, more residual oil is obtained compared to without irradiation. It has also been shown that changing the viscosity of dielectric nanofluids during electromagnetic irradiation increases sweep efficiency, resulting in higher oil recovery.